Internationalization of Higher Education in MENA : Policy Issues Associated with Skills Formation and Mobility - Jaramillo, Adriana (World Bank, Washington, DC, 2014)
This policy issues note is focused on internationalization of higher education and the linkages and implications that internationalization has for skills mobility. Internationalization is one of the most important developments that globalization has brought to higher education worldwide. In the Middle East and North Africa (MENA) region, it has turned into quite a complex undertaking. The Arab Spring has made it clear that young people in MENA are asking for more and better opportunities: to study and work; to move about the world; and to learn and to create new knowledge and enterprises. Higher education, migration, and labor mobility are key policy areas as MENA nations address the need for a strong skills base to underpin the economic and social development of the regions disparate economies. All three policy areas share an interest in the development, recognition, and application of educational qualifications, in the quality of education and training, and in the ability of people to acquire, provide, and use education for their own well-being and for their nation's benefit. This note is intended to be the base document for a policy dialogue integrating the three issues associated with the development of human capital: higher education, migration, and labor mobility. This note seeks to introduce a systematic policy discussion about the internationalization of higher education to help MENA countries improve the quality and relevance of their higher education systems, open opportunities for better skills development, and improve high-skilled labor migration. There are important interactions among the formation of skills and competencies, the acquisition of credentials and qualifications, and where and how those skills are applied. These include the quality of education, the ease with which credentials are recognized in different countries, the role of international partners, and the incentives to study and work in the region and elsewhere. This note will explore how a regional approach to accreditation and recognition of qualifications could bring benefits and understanding of the complex interactions among student mobility, domestic higher education, and the economic and social development priorities of MENA countries. It will also provide evidence on the importance of setting goals for intra-regional student mobility and for student and faculty flows into the region through accreditation, student and faculty exchange, hiring incentives, and research infrastructure including competitive research grants. Finally, the note will demonstrate the need for a clear policy on the 'export of educational services.'